Analisis Penerimaan Mahasiswa Baru dengan Penentuan Strategi Keunggulan Bersaing - Shafiq Nurdin; Riski Nur Istiqomah Dinnullah (Department of Industrial Engineering Universitas Muhammadiyah Surakarta, 2017)
The strategy will determine the competitive advantage of the organization, including the college. The right strategy in the admission of new students needs to be formulated. Faculty of Engineering Universitas Merdeka Malang need to formulate strategy in acceptance of new student. The data used is taken in 2015. The data collected is then analyzed using Value Chain analysis. Five attributes of competitive advantage are majors, physical facilities, tuition fees, location, and promotion. The strategy is consolidation that is defensive, avoiding market loss by strengthening the loyalist network, horizontal integration with more effort to expand the market that has not been absorbed maximally, to penetrate the market and develop the department. The appropriate strategy developed in increasing the competitive advantage of Unmer Faculty of Engineering Malang is a focus strategy. This focus strategy is directed to differentiation, where the Faculty of Engineering seeks to achieve differentiation within its target segment.